2006
DOI: 10.1097/01.mlg.0000224348.44616.fb
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Duty Hour Restrictions on Otolaryngology Training: Divergent Resident and Faculty Perspectives

Abstract: Otolaryngology programs have successfully restricted resident duty hours through significant infrastructural changes. Of concern, the majority of residents surveyed appeared to be in favor of the ACGME restrictions, whereas most program directors and faculty were opposed. Further studies are needed to establish whether limited work hours will enhance or hinder the residency training experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 11 publications
2
58
0
Order By: Relevance
“…Following this recommendation, a study examining the impact of these restrictions on residency training programmes from the residents' perspectives showed that most residents (67%) agreed that their mental health had improved. [14] This finding corroborates the findings of our study of the association of perceived excessive work with psychological distress.…”
Section: Discussionsupporting
confidence: 83%
“…Following this recommendation, a study examining the impact of these restrictions on residency training programmes from the residents' perspectives showed that most residents (67%) agreed that their mental health had improved. [14] This finding corroborates the findings of our study of the association of perceived excessive work with psychological distress.…”
Section: Discussionsupporting
confidence: 83%
“…Similar sentiments have been echoed in the otolaryngology literature, in which 69% of the otolaryngology faculty reported that the implementation of resident duty-hour restrictions had a negative effect on resident education. 3 Family medicine program directors have also expressed significant concerns about the consequences of resident duty-hour reforms, for example, decreases in professionalism among residents because of a shift mentality, the loss of continuity of care, a decrease in formal education opportunities, and the creation of expectations that may be inconsistent with the realities of practice. 10 Only 4% of program directors thought the residents fared better overall under the new regulations.…”
Section: Discussionmentioning
confidence: 99%
“…However, these reforms are relatively recent. 5,6,11,14 As younger physicians begin to practice, particularly in academics, it will be interesting to see if perceptions and attitudes are ultimately different between the old and new generation of trainees. Similarly, sex did not have any effect on faculty perceptions, though women residents have previously been more favorable toward the changes than men.…”
Section: Commentmentioning
confidence: 99%